Tuberculosis and risk of coronary heart disease: A systematic review and meta-analysis - Wasit Wongtrakul (2020)
© 2020 Tuberculosis Association of India Background: Increased risk of coronary heart disease has been observed in several chronic inflammatory disorders, including chronic infection. However, data on the association between tuberculosis and risk of coronary heart disease are limited. Methodology: This systematic review and meta-analysis identified all cohort studies that compared the risk of coronary heart disease among patients with tuberculosis versus individuals without tuberculosis and summarized their results together. Literature search was independently conducted by two investigators using MEDLINE and EMBASE database up to August 2019. Point estimates and standard errors from each study were pooled together using the generic inverse variance method of DerSimonian and Laird. Results: A total of four cohort studies met the eligibility criteria and were included into the meta-analysis. The pooled analysis found that patients with tuberculosis have an increased risk of developing coronary heart disease with the pooled risk ratio of 1.76 (95% CI, 1.05–2.95; I2 of 97%). Conclusion: A significantly increased risk of coronary heart disease among patients with tuberculosis was demonstrated by the current study.